Ambulatory Monitoring of Blood Pressure in Occupational Hypertension - Saturnino Suárez Ortega; Noel Lorenzo Villalba; Saray Hernández Valiente (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
Stress is considered to have a strong impact on changes in blood pressure through overproduction of catecholamines during working hours [1,2]. We are presenting the graphical behavior of blood pressure of two patients. In both cases hypertension is present exclusively during working hours. The first graphic correspond to a 39 year old nurse working 7 hours (Figure 1) and the second one, to a 46 year old engineer working from 8:00 am to 22:00 pm. In the second case, this period also included a two hour-lunch break and nap break.